KRAKTERISTIK TAFSIR NUSANTARA DALAM KITAB TAFSIR AL-QUR’AN AL’AZHIM KARYA RADEN PENGHULU TABSHIR ANAM V - Rafiqul Huda Siregar (PERADA, 2022)
Tafsir is a process to understand the meaning contained in the Qur'an. One of the interpretations is Tafsir al-Qur'an al-'Azhim. This interpretation is the work of the Nusantara cleric Raden Pengulu Tabshir Anam V. This paper is examined with a theoretical framework of approaches in the study of interpretation. What is meant by the approach method is the mindset (al-Ittijah al-Fikri) used to discuss a problem in an interpretation. Then it can be concluded that the method used by Raden Pengulu Tabshir Anam V in his interpretation is when viewed in terms of the source of his interpretation, namely using the bi al-ma'tsur method. If viewed from the perspective of how the explanation is included in the bayaani method / description. As for when viewed in terms of the breadth of the explanation of the interpretation, including using the Ijmali method. And when viewed from the point of view of the goals and order of the verse, it includes the Tahlili method.